Deficiency of IFNAR1 Increases the Production of Influenza Vaccine Viruses in MDCK Cells - Wang, Qi; Chen, Tuanjie; Feng, Mengru; Zheng, Mei; Gao, Feixia; Qiu, Chenchen; Luo, Jian; Li, Xiuling (Viruses, 2025)
Cell culture-based influenza vaccines exhibit comparable safety and immunogenicity to traditional egg-based vaccines. However, improving viral yield remains a key challenge in optimizing cell culture-based production systems. Madin–Darby canine kidney (MDCK) cells, the predominant cell line for influenza vaccine production, inherently activate interferon (IFN)-mediated antiviral defenses that restrict viral replication. To overcome this limitation, we employed CRISPR/Cas9 gene-editing technology to generate an IFN alpha/beta receptor subunit 1 (IFNAR1)-knockout (KO) adherent MDCK cell line. Viral titer analysis demonstrated significant enhancements in the yield of multiple vaccine strains (H1N1, H3N2, and type B) in IFNAR1-KO cells compared to wild-type (WT) cells. Transcriptomic profiling revealed marked downregulation of key interferon-stimulated genes (ISGs)—including OAS, MX2, and ISG15—within the IFNAR1-KO cells, indicating a persistent suppression of antiviral responses that established a more permissive microenvironment for influenza virus replication. Collectively, the engineered IFNAR1-KO cell line provides a valuable tool for influenza virus research and a promising strategy for optimizing large-scale MDCK cell cultures to enhance vaccine production efficiency.